Innovation of Marketing Strategies in the Tourism Market under the Background of Smart Tourism - Yu, Luning (Transactions on Economics, Business and Management Research, 2024)
In the development of modern tourism, smart tourism, as a major direction, signifies the deep integration of information technology and the tourism industry. To achieve established goals, organizations need to keep pace with the times and continually adapt to and lead the new trends in industry development. In specific practice, conducting thorough market research is essential. The current tourism market exhibits diversified and personalized consumption characteristics, requiring organizations to deeply understand consumer needs and preferences to provide more accurate and efficient services. Through big data analysis and artificial intelligence technology, organizations can more precisely grasp market dynamics, providing strong support for the formulation of marketing strategies. In various marketing events, organizations should be based on development, continually summarizing experiences, exploring innovative paths, and through cross-industry cooperation, more tourism industry marketing resources can be tapped to achieve effective connection between the tourism industry and other industry structures, promoting diversified development of regional economy.